1998
DOI: 10.1051/analusis:199826040064
|View full text |Cite
|
Sign up to set email alerts
|

Potential of two-dimensional correlation spectroscopy in analyses of NIR spectra of biological fluids. I. Two-dimensional correlation analysis of protein and fat concentration-dependent spectral variations of milk

Abstract: T wo-dimensional (2D) corre l ation spectro s c o py has recently received keen interest because it is a totally n ew and powerful spectral analytical method [1][2][3][4]. The 2D correlation spectroscopy enables us to obtain spectral information not readily accessible from one-dimensional spectra by spreading spectral peaks over the second dimension [1][2][3][4][5][6][7]. Band assignments and studies of inter-and intramolecular interactions become easier by selective correlations between various bands in synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
0
19
0
4
Order By: Relevance
“…Summing up the above analysis results and referring to corresponding literature [8][9][10][11][12][13][14], we present the assignments of NIR bands in Table 2. CH str and CC str .…”
Section: Assignments Of Nir Bandsmentioning
confidence: 99%
“…Summing up the above analysis results and referring to corresponding literature [8][9][10][11][12][13][14], we present the assignments of NIR bands in Table 2. CH str and CC str .…”
Section: Assignments Of Nir Bandsmentioning
confidence: 99%
“…milk quality analysis, has witnessed greater research activity. 26,27,[29][30][31][32]35 Wang et al 35…”
Section: Milk Quality Determinationmentioning
confidence: 99%
“…Fluid fat and protein reflectance 800-1100 nm Huang et al 27 fat and protein transflectance 1100-2500 nm Wang et al 35 fat and protein transmittance 1100-2500 nm purnomoadi et al 29 fat, protein and lactose transmittance 800-1100 nm Šašić & ozaki 30 unhomogenised milk composition transmittance 700-2400 nm tsenkova et al 31 unhomogenised milk composition transmittance 1100-2400 nm tsenkova et al 32 Somatic cell count transmittance 400-1100 nm pravdova et al 28 Somatic cell count transflectance 1100-2500 nm tsenkova et al 33 Somatic cell count transmittance 700-1100 nm tsenkova et al 34 reported that two-dimensional (2d) correlation spectroscopy in the nIr region could be used for the analysis of fat and protein in milk; this procedure revealed the existence of a number of hidden bands and also helped explain why certain wavelengths were selected in chemometric calibration models. 2d correlation spectroscopy enables spectral information not readily accessible from one-dimensional spectra to be obtained by spreading spectral peaks over a second dimension.…”
Section: Countrymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in which concentration is the 'perturbation' variable include a 2D NIR analysis of fat and protein in milk [25], a 2D IR study of polymer blends and copolymers [26][27][28] and a 2D IR study of antioxidants in aircraft engine oil [29]. Surprisingly, there have been relatively few reports of 2D correlation spectroscopy being applied in process monitoring analysis or application of the generalised 2D method to NMR analysis.…”
Section: Introductionmentioning
confidence: 99%